2021
DOI: 10.1016/j.isci.2021.102196
|View full text |Cite
|
Sign up to set email alerts
|

Impaired phosphatidylethanolamine metabolism activates a reversible stress response that detects and resolves mutant mitochondrial precursors

Abstract: Phosphatidylethanolamine (PE) made in mitochondria has long been recognized as an important precursor for phosphatidylcholine production that occurs in the endoplasmic reticulum (ER). Recently, the strict mitochondrial localization of the enzyme that makes PE in the mitochondrion, phosphatidylserine decarboxylase 1 (Psd1), was questioned. Since a dual localization of Psd1 to the ER would have far-reaching implications, we initiated our study to independently re-assess the subcellular distribution of Psd1. Our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 98 publications
(122 reference statements)
0
10
0
Order By: Relevance
“…The endomembrane system may suffer from a lower PE level or from a shortage of specific PE molecular species that are insufficiently supplied from the mitochondria. The notion that a minimum of PE synthesized in the ER is required for optimal growth is supported by the recent finding that several independent Psd1 constructs that localize exclusively to the mitochondrial inner membrane do rescue the ethanolamine auxotrophy of a psd1Δpsd2Δ mutant in which Dpl1p supplies the CDP‐ethanolamine route with phosphoethanolamine (Sam et al , 2021 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The endomembrane system may suffer from a lower PE level or from a shortage of specific PE molecular species that are insufficiently supplied from the mitochondria. The notion that a minimum of PE synthesized in the ER is required for optimal growth is supported by the recent finding that several independent Psd1 constructs that localize exclusively to the mitochondrial inner membrane do rescue the ethanolamine auxotrophy of a psd1Δpsd2Δ mutant in which Dpl1p supplies the CDP‐ethanolamine route with phosphoethanolamine (Sam et al , 2021 ).…”
Section: Resultsmentioning
confidence: 98%
“…A twist to the longstanding concept of PSD activity residing exclusively outside the ER, came with the recent finding of a dual localization of Psd1p to mitochondria and ER, the distribution depending on metabolic demand (Friedman et al , 2018 ). However, the presence of a functional subpopulation of Psd1 in the ER was not confirmed in an independent re‐evaluation (Sam et al , 2021 ), leaving it under debate.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the ER-localized Psd1 pool is less abundant than mitochondrial Psd1 and is difficult to detect, particularly in nutrient-rich or respiratory-demanding growth conditions ( Friedman et al. , 2018 ; Sam et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…( Friedman et al., 2018 ). However, most Psd1 was detected as a mitochondria-localized form, whereas only a small amount of ER-localized Psd1 was found in the heavy membranes ( Figure 4 L) ( Sam et al., 2021 ). We also confirmed that amounts of phospholipid synthetic enzymes such as Cho1, Psd1, Cho2, and Opi3 were comparable or increased in the membrane fractions isolated from DTT- or tunicamycin-treated cells compared with those of control membranes ( Figure 4 L).…”
Section: Resultsmentioning
confidence: 99%